Bakteri Pendegradasi Selulosa dari Serasah Daun Avicennia alba Blume di Kawasan Hutan Mangrove Peniti Kabupaten Pontianak - Irwan Lovadi, Rizqie Lestya Ningsih, Siti Khotimah, (Universitas Tanjungpura, 2014)
Avicennia alba is a plant that dominated in Peniti Mangrove Forest Pontianak regency. So many found leaf litter the region. Microorganism like celulotic bacterial has important role to degrade selulose in the litter. The aim of this study is to know genus selulose degrading bacterial in litter leaf of A. alba at Peniti Mangrove Forest. Sampel of litter leaf has taken by Composite Sampling Methode with 10 spot in 3 different location. Bacterial isolating by Pour Plate Methode with CMC selectif medium and the using sea water (environmental litter) for manufacturing suspension. The isolate bacterial was describe use coloni morphology test, cell morphology, and biochemistry. The result of isolation was found 14 pure isolation and after the identification was found 8 genera they are Pseudomonas, Plesiomonas, Pasteurella, Neisseria, Actinobacillus, Corynebacterium, Aeromonas, Vibrio